Clinical outcomes of newly diagnosed PCNSL treated with rituximab-methotrexate-cytarabine with or without ibrutinib: a retrospective study - Wang, Wenhua; Wang, Bingyi; Sun, Yifei; Qiu, Lihua; Qian, Zhengzi; Zhou, Shiyong; Song, Zheng; Li, Wei; Zhang, Xudong; Li, Lanfang; Wang, Xianhuo; Zhang, Huilai (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to evaluate the efficacy and safety of rituximab, methotrexate, cytarabine with or without ibrutinib in newly diagnosed primary central nervous system lymphoma (PCNSL) and explore the correlation between efficacy and genomic alterations.MethodsFrom March 2013 to October 2022, data from 88 patients with newly diagnosed PCNSL were retrospectively collected and analyzed. Fifty-nine patients received rituximab, methotrexate and cytarabine (RMA, group A), and twenty-nine patients received the same RMA combined with ibrutinib (RMA + Ibrutinib, group B).ResultsAt a median follow-up of 27.7 months, the complete response rate (CRR), overall response rate (ORR) and overall survival (OS) in group B superior to group A (41.4% versus 16.9% for CRR, P=0.013; 86.2% versus 59.3% for ORR, P=0.011; P=0.036 for OS). The ORR, progression-free survival (PFS) and OS of RMA + ibrutinib +deep lesions (group C) were better than those of RMA + deep lesions (group D) (P=0.027 for ORR, P=0.046 for PFS, P=0.004 for OS). Patients in group B had no more toxicities than those in group A and the most common adverse events in the two groups were primarily grade 1-2. Sequencing of tumor tissues from 22 patients showed that MYD88 mutations were the most frequent genetic alterations, two patients with CARD11 mutation did not respond to treatment and three patients without an MYD88 or CD79B had response after treatment.ConclusionsRMA in combination with ibrutinib regimen improved response rates and survival in newly diagnosed PCNSL with no serious adverse effects. Mutations in CARD11 gene may provide directions for patients to select targeted drugs.